(untitled) (International journal of artificial intelligence, 2026)
This article examines the military genius and historical significance of Zahiriddin Muhammad Babur, focusing on the factors behind his remarkable victories and enduring legacy. Particular attention is given to Babur’s early military training, his rapid rise to power at a young age, and his innovative tactical approaches during his campaigns in India. The article explores the strategic methods he employed, including mobility, ambush tactics, feigned retreats, and the tulghama maneuver, which enabled him to defeat numerically superior forces. Furthermore, the paper discusses Babur’s role in founding the Mughal Empire and unifying fragmented territories into a centralized state.